2018
DOI: 10.21053/ceo.2017.01375
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptable Noise Level Benefit From Directionality for Listeners With Severe Hearing Loss

Abstract: Objectives Directional microphone technology can enhance the speech intelligibility and listening comfort of listeners with hearing impairment. The main aim of this study is to investigate and compare the benefit derived by listeners with severe hearing loss from directional microphone technology with that derived by listeners with moderate hearing loss.Methods The acceptable noise levels (ANLs) of two groups of listeners with moderate or severe hearing impairment (17 subjects in each group) were measured unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The ANL improvement in our study is 4.44 dB and 3.72 dB for the directional-multichannel and the broadband DNR conditions, respectively. The results of the present study are consistent with those of other studies [ 8 , 11 , 19 , 21 , 24 ] and suggest it is most appropriate to use of both DIR and DNR algorithms. However, these results are limited to our specific study design as well as the laboratory findings because it has been shown the subject benefit depends on both the type of DSP employed by the hearing aid [ 8 , 11 ] and there may not DSP benefits in real life conditions because of reverberation or different types of noises.…”
Section: Discussionsupporting
confidence: 92%
“…The ANL improvement in our study is 4.44 dB and 3.72 dB for the directional-multichannel and the broadband DNR conditions, respectively. The results of the present study are consistent with those of other studies [ 8 , 11 , 19 , 21 , 24 ] and suggest it is most appropriate to use of both DIR and DNR algorithms. However, these results are limited to our specific study design as well as the laboratory findings because it has been shown the subject benefit depends on both the type of DSP employed by the hearing aid [ 8 , 11 ] and there may not DSP benefits in real life conditions because of reverberation or different types of noises.…”
Section: Discussionsupporting
confidence: 92%
“…Rather, UHL has been regarded as "a happy feature of a misfortune" because affected children show generally normal development [6]. The treatment options for UHL range from no intervention to FM amplification systems, conventional hearing aids, hearing aids with contralateral routing of signals, bone-anchored hearing aids, and cochlear implantation [28][29][30][31]. However, in real-world clinical situations, the majority of young people with UHL only receive preferential seating at the front of the class and are educated on the importance of protecting the contralateral ear with normal hearing.…”
Section: Discussionmentioning
confidence: 99%
“…An omnidirectional microphone was set for all participants, and other digital signal processing algorithms (such as Sound Smoothing, eWind Screen, and Feedback Stopper) were inactivated. Based on the protocol introduced by Shahid Beheshti University of Medical Sciences (BUMS) for fitting the digital processing hearing aid, each participant was evaluated using the calibrated version of the Ling-6 sounds for evaluation of aided detection thresholds [16][17][18]. Despite the fact that DIN test was accomplished in suprathreshold level, the hearing aid was fitted so that the Ling-6 sounds were audible and discriminative in the level of 30 dB HL to provide equal audibility for all subjects.…”
Section: Hearing Aid Fittingmentioning
confidence: 99%